"We're in the background": Facilitators and barriers to fathers' engagement and participation in a health intervention during the early parenting period. (28th October 2020) - Seymour, Monique; Peace, Ryan; Wood, Catherine E.; Jillard, Chris; Evans, Kirsty; O'Brien, Jacquie; Williams, Le Ann; Brown, Stephanie; Giallo, Rebecca
Abstract: Issues addressed: Little is known about the barriers and facilitators associated with engaging fathers in interventions targeting their physical and mental health. The current research therefore aimed to explore fathers' perceived barriers and facilitators to engagement and participation in a health intervention delivered during the early parenting period. Methods: Eleven fathers of young children (0‐4 years) were interviewed about their perceptions and experiences of facilitators and barriers to engaging and participating in an intervention ( Working Out Dads ) to target their mental and physical health. Interviews were recorded and transcribed. Transcripts were analysed using thematic analysis. Results: Fathers identified a number of program‐related and father‐related facilitators and barriers which impacted their engagement and participation. Program‐related facilitators included: accessibility of the program; father advocacy of the program; group fitness/exercise component; and having a father‐specific program. Facilitating factors related to fathers included: making social connections; learning how to be a better dad/partner; and partner support and encouragement to attend. Program‐related barriers included: travel; lack of awareness; and gender roles. While father‐related barriers included: being time poor; sacrifices to family; and apprehension. Conclusions: The current findings identified many areas that facilitate, encourage and motivate men to participate in interventions which support their mental and physical health during the early parenting period. Relevance: Generating evidence on barriers and facilitators to health interventions is important to improving the current intervention along with informing the development of engaging and targeted health interventions for fathers in early parenthood.